2015
DOI: 10.1007/s11192-015-1814-0
|View full text |Cite
|
Sign up to set email alerts
|

Data integration for research and innovation policy: an Ontology-Based Data Management approach

Abstract: This paper proposes an Ontology-Based Data Management (OBDM) approach to coordinate, integrate and maintain the data needed for Science, Technology and Innovation (STI) policy development. The OBDM approach is a form of integration of information in which the global schema of data is substituted by the conceptual model of the domain, formally specified through an ontology. Implemented in Sapientia, the ontology of multi-dimensional research assessment, it offers a transparent platform as the base for the asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 20 publications
0
32
0
Order By: Relevance
“…They do not solve the issue of comparability and standardisation of information and of inter-operability, updating and scalability of databases (Daraio & Glänzel, 2016). However, recent developments in engineering in computer science could be helpful and should be further explored to address these issues (Daraio, Lenzerini, Leporelli, Moed, et al, 2016). Daraio and Bonaccorsi (2017) illustrate the design of a possible information system to integrate microdata on universities with other sources with the aim of overcoming rankings by linking data in an open platform.…”
Section: Re S E Arch and Hi G Her Educ Ati On In Today ' S So Cie T Ymentioning
confidence: 99%
“…They do not solve the issue of comparability and standardisation of information and of inter-operability, updating and scalability of databases (Daraio & Glänzel, 2016). However, recent developments in engineering in computer science could be helpful and should be further explored to address these issues (Daraio, Lenzerini, Leporelli, Moed, et al, 2016). Daraio and Bonaccorsi (2017) illustrate the design of a possible information system to integrate microdata on universities with other sources with the aim of overcoming rankings by linking data in an open platform.…”
Section: Re S E Arch and Hi G Her Educ Ati On In Today ' S So Cie T Ymentioning
confidence: 99%
“…Turko et al, [15] program found effective for gaining top positions in the world universities rankings by prioritizing university aims and enhancing its worth. Recently, Daraio et al, [16] proposed a method for data management which is based on ontology to identify, maintain and integrate the data required for STI policy making. They implemented Sapientia, an ontology of multidimensional research assessment.…”
Section: Related Workmentioning
confidence: 99%
“…An OBDM approach may be considered to be a kind of information integration based on: a) a conceptual description of the knowledge domain of interest, called the ontology; b) the different databases where the data of the domain is kept, called the sources; c) the correspondences between the data contained in the sources and the concepts of the ontology, called the mappings. The main advantages of an OBDM approach for integrating research and other scholarly data (Daraio et al, 2016a) are: accessibility of the data through the elements of the ontology; explicit representation of the domain, facilitating the re-usability of the acquired knowledge; explicit specification of the relationships between the domain concepts and the data through the mappings, facilitating documentation and standardization; flexibility of the integrated system that does not require the integration of all the data sources at once; extensibility of the system by means of incremental addition of new data sources or new concepts when they become available.…”
Section: Datamentioning
confidence: 99%
“…Figure 2 shows the role of our modeling framework in its interplay with the empirical and policy world for the understanding of the real world. We claim that the more the Quality is conceptually and formally specified, the more the overlapping  Within some research projects funded by Sapienza University in 2013 and 2015 we did an experiment of a knowledge infrastructure, a case of an "open science of science" exercise, around Sapientia: The Ontology of Multi-Dimensional Research Assessment (Daraio et al, 2016a;2016b). Sapientia represents an effort of going toward a common platform which can show which data has to be collected; by offering the opportunity of making analysis under different perspectives, testing different models, but sharing the same common conceptual characterization.…”
Section: Toward Responsible Metrics?mentioning
confidence: 99%